(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Balinese traditional architecture constitutes a significant cultural legacy enriched with philosophical, societal, and ecological meanings; however, its continuity is increasingly challenged by the pressures of modernization, rapid urban expansion, and the declining transmission of indigenous knowledge across generations. This study investigates the function of integrating digital technologies as a conservation strategy aimed at reinforcing long-term cultural sustainability. A qualitative-descriptive approach is adopted through comprehensive literature review, on-site observation, and case-study examination of the digitalization processes applied to traditional architectural structures. The findings indicate that digital recording techniques (3D scanning, photogrammetry) together with immersive educational visualization (augmented reality/AR, virtual reality/VR) significantly improve the precision of heritage documentation, generate opportunities within the creative economy, support cultural learning initiatives, and enhance the involvement of local communities. Nevertheless, several major constraints remain, including limited digital literacy among stakeholders, inadequate technological infrastructure, cultural hesitation toward technological intervention, and the absence of coherent and integrative policy frameworks. Based on these findings, a strategic framework identified as the “Digital-Integrated Cultural Sustainability (DICS)” model is formulated, combining advanced digital applications with indigenous cultural principles to achieve sustainable preservation. This research ultimately demonstrates that digital technology should not be regarded merely as a technical instrument, but rather as an innovative and strategic mechanism for safeguarding the tangible and intangible cultural values of Bali. It is expected that these outcomes may provide practical guidance for the formulation of digital-oriented conservation policies and implementation strategies within other regions possessing rich cultural heritage. properly, and there are gaps in the connection between units.